Impact of Key Assumptions on Model Performance. - Kewei Wang (556371) (2025)
(A): Impact of Demand Uncertainty on Transport Cost, Carbon Emission, and Freshness Loss; (B): Impact of Vehicle Heterogeneity on Carbon Emission and Transport Cost; (C): Impact of Traffic Uncertainty on Travel Time.